Emparejamiento selectivo por edad y educación en la formación de uniones: una revisión de la investigación en América Latina - Robles, Adriana (El Colegio de México A.C., 2024)
The objective of this article is to present a review of the literature on age and educational assortative mating in Latin America in the last two decades. There is extensive research around educational assortative mating in the region while exploring more elements about age assortative mating is still necessary. The thematic coverage of the research produced, particularly in the last decade around educational assortative mating, is extensive and contributes significantly to the global discussion. On the other hand, the review of the analysis of age assortative mating reveals that there are still lines of research to be explored on this subject, particularly in a context such as Latin America, characterized by economic and gender inequality, uncertainty in the labor market, and heterogeneity in the demographic transition.